Kajian Kritis Terhadap Dualisme Pengadilan Elektronik (E-Court) dan Konvensional - Khotib Iqbal Hidayat; Aris Priyadi; Elly Kristiani Purwendah (Batulis Civil Law Review, 2020)
This study aims to determine how the application of electronisc justice system (e-Court) in providing the principle of benefit for the parties in civil cases. This study uses a normative juridical approach with secondary data sources supported by primary data. The results showed that the existence of electronisc justice system (e-Court) can provide the principle of benefit for the parties including transparency of the process, cost, and time efficiency for justice seekers who are able to access IT (Information Technology) and the existence of dualism is still needed for justice seekers which still requires conventional proceedings due to limited access to IT (Information Technology).